(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The objective of this exploratory study is to understand the various perspectives of children’s parliament involved in the process of growth. The researcher used purposive sampling to collect data from 450 members of 30 children’s parliaments (CP). Frequency tables and diagrams were adopted for the analysis of the data. Attachment of parents and children, relationship with peers and teachers were found to influence their growth. Through Venn diagram and social mappings, the children identified with misunderstandings and finance were the major sources of conflicts. Children’s parliaments played a key role in their holistic development, namely, biological, personality, social, political, cultural, communitarian, ethical and ecological dimensions.